2021
DOI: 10.1371/journal.pone.0250238
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of textual elements on the comprehensibility of drug label instructions (DLIs): A systematic review

Abstract: Introduction Correct interpretation of drug labels instructions (DLIs) is needed for safe use and better adherence to prescribed drugs. DLIs are often too difficult for patients, especially for those with limited health literacy. What is yet unknown, is how specific textual elements in DLIs (e.g., the presentation of numbers, or use of medical jargon) and patients’ health literacy skills are related to the comprehension of DLIs. In order to provide concrete directions for health professionals on how to optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Therefore, health education focusing on communicative or critical HL, rather than just providing knowledge, would be effective in improving the understanding of medication package inserts. Furthermore, development of more readable and an improved format could contribute to the understanding of medication package inserts [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, health education focusing on communicative or critical HL, rather than just providing knowledge, would be effective in improving the understanding of medication package inserts. Furthermore, development of more readable and an improved format could contribute to the understanding of medication package inserts [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor labeling of prescription drugs and patient nonnoncompliance to prescribed medicines is major reason for outpatient medication errors and adverse events (2-4) (10,11). A systematic review conducted to evaluate the impact of textual elements on the comprehensibility of drug label instructions (DLIs) showed that using clear labels about dosage instructions sing plain language can improve patient understanding of dosage instructions (24).…”
Section: Discussion 41 General Description Of the Studymentioning
confidence: 99%
“…Researchers have long studied how to best provide comprehensive medication information related to medication use and understanding in a simplistic and practical manner. As such, numerous studies related to this topic have been published ( Maghroudi et al, 2021 ). Studies have focused on factors such as, complexity of dosing instructions particularly in relation to patient health literacy ( Beckman et al, 2005 ; Shrank et al, 2007 ; European Commission, 2009 ; Bailey et al, 2012 ; Emmerton et al, 2012 ; Koster et al, 2014 ; Patel et al, 2018 ), requirements concerning content an comprehensibility of the text ( Raynor and Bryant, 2013 ; Pires et al, 2016 ; Yuan et al, 2019 ), precision of writing dosing instructions ( Borgsteede and Heringa, 2019 ), and the use of icons, graphics and pictograms ( Kheir et al, 2014 ; van Beusekom et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies have focused on communication of medicines information, format and organization of the medicines label, as well as number of medicines dispensed ( Wolf et al, 2007 ; Bailey et al, 2012 ; Emmerton et al, 2012 ; Samaranayake et al, 2018 ). There is attention for improving the PDL texts ( Maghroudi et al, 2018 ; Maghroudi et al, 2021 ), which has improved the labels. However, the ideal approach to bundle these aspects still remains unclear.…”
Section: Introductionmentioning
confidence: 99%